Whole genome sequencing of 45 Japanese patients with intellectual disability - Abe‐Hatano, Chihiro; Iida, Aritoshi; Kosugi, Shunichi; Momozawa, Yukihide; Terao, Chikashi; Ishikawa, Keiko; Okubo, Mariko; Hachiya, Yasuo; Nishida, Hiroya; Nakamura, Kazuyuki; Miyata, Rie; Murakami, Chie; et al. (American journal of medical genetics. Part A, 2021)
Intellectual disability (ID) is characterized by significant limitations in both intellectual functioning and adaptive behaviors, originating before the age of 18 years. However, the genetic etiologies of ID are still incompletely elucidated due to the wide range of clinical and genetic heterogeneity. Whole genome sequencing (WGS) has been applied as a single‐step clinical diagnostic tool for ID because it detects genetic variations with a wide range of resolution from single nucleotide variants (SNVs) to structural variants (SVs). To explore the causative genes for ID, we employed WGS in 45 patients from 44 unrelated Japanese families and performed a stepwise screening approach focusing on the coding variants in the genes. Here, we report 12 pathogenic and likely pathogenic variants: seven heterozygous variants of ADNP, SATB2, ANKRD11, PTEN, TCF4, SPAST, and KCNA2, three hemizygous variants of SMS, SLC6A8, and IQSEC2, and one homozygous variant in AGTPBP1. Of these, four were considered novel. Furthermore, a novel 76 kb deletion containing exons 1 and 2 in DYRK1A was identified. We confirmed the clinical and genetic heterogeneity and high frequency of de novo causative variants (8/12, 66.7%). This is the first report of WGS analysis in Japanese patients with ID. Our results would provide insight into the correlation between novel variants and expanded phenotypes of the disease.